2018
DOI: 10.1098/rsob.180078
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules play a role in trafficking prevacuolar compartments to vacuoles in tobacco pollen tubes

Abstract: Fine regulation of exocytosis and endocytosis plays a basic role in pollen tube growth. Excess plasma membrane secreted during pollen tube elongation is known to be retrieved by endocytosis and partially reused in secretory pathways through the Golgi apparatus. Dissection of endocytosis has enabled distinct degradation pathways to be identified in tobacco pollen tubes and has shown that microtubules influence the transport of plasma membrane internalized in the tip region to vacuoles. Here, we used different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
2
3
0
Order By: Relevance
“…These findings challenge the assumed notion that, other than in secretion, microtubules have little involvement in vesicle and organelle movement in plants (28). In this challenge, our work joins other recent reports suggesting a role for microtubules in TGN biogenesis and tracking (74) and in trafficking between the MVB and the vacuole (75).…”
Section: Discussionsupporting
confidence: 78%
“…These findings challenge the assumed notion that, other than in secretion, microtubules have little involvement in vesicle and organelle movement in plants (28). In this challenge, our work joins other recent reports suggesting a role for microtubules in TGN biogenesis and tracking (74) and in trafficking between the MVB and the vacuole (75).…”
Section: Discussionsupporting
confidence: 78%
“…The findings described in this section were mainly achieved using lily flower pollen, which has been widely used to study the growth kinetics of pollen tubes due to its rapid elongation property. A similar polarized distribution of vacuoles has been observed in other species, such as Arabidopsis and tobacco [ 16 , 42 , 43 ], implying that the homologous mechanism controlling vacuole dynamics might be conserved in angiosperms.…”
Section: Developmental Processessupporting
confidence: 73%
“…A previous study showed that the disruption of MTs by oryzalin did not cause any obvious defects in vacuolar status, suggesting that actin, rather than MTs, is primarily engaged in the maintenance of vacuolar morphology and distribution in pollen tubes [ 41 ]. However, a more recent report indicated that MTs are required for transporting prevacuolar compartments to large vacuoles in the shank of tobacco pollen tubes, which points to the possibility of MTs engagement in fine-tuning vacuolar dynamics [ 42 ].…”
Section: Developmental Processesmentioning
confidence: 99%
“…It has been shown that microtubules play an important role in abiotic stress due to changes in their location and structural organization and can cause changes in cell size [60][61][62]. Atypical components of the cytoskeleton in tomato root cells exposed to NaCl and Na 2 SO 4 at different levels of ROS, as well as shortening and thinning of microtubules, were observed in the cytoplasm of tobacco root cells in longitudinal and transverse sections [63].…”
Section: Discussionmentioning
confidence: 96%